2022
DOI: 10.1002/ceas.12243
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement and counseling skill self‐efficacy: Comparing two course formats

Abstract: A between‐group, repeated‐measures study compared sections of a career counseling course. One course used a flipped classroom design, while the other used a lecture. The flipped classroom yielded higher ratings of career counseling self‐efficacy and active engagement among students. There were no differences in helping skills self‐efficacy between the courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…First, they practiced through social media, video games, robots, and virtual reality [43][44][45][46]. They also utilized innovative pedagogy and techniques such as online learning, cyber counseling, and flipped learning [47][48][49]. However, the most common application in counseling is online counseling, where the Internet is the delivery medium [4] [48].…”
Section: Technology Integration In Counseling and Mental Health Educa...mentioning
confidence: 99%
See 1 more Smart Citation
“…First, they practiced through social media, video games, robots, and virtual reality [43][44][45][46]. They also utilized innovative pedagogy and techniques such as online learning, cyber counseling, and flipped learning [47][48][49]. However, the most common application in counseling is online counseling, where the Internet is the delivery medium [4] [48].…”
Section: Technology Integration In Counseling and Mental Health Educa...mentioning
confidence: 99%
“…Researchers conducted several studies to explore the impact of using technology in the counseling and mental health fields; for example, [49] conducted a quasi-experimental study that revealed the flipped learning method returned higher career counseling self-efficacy and active engagement among students than the lecture method. Further, [47] conducted a descriptive study among Turkish counselors; the study involved 542 counselors who are members of the Turkish Psychological Counseling and Guidance Association.…”
Section: Technology Integration In Counseling and Mental Health Educa...mentioning
confidence: 99%
“…As programs now return to the campus classroom, some students remain unable for various reasons. While there is some evidence for using a flipped classroom design in general counseling (Mason et al, 2022), there is little evidence for the effectiveness of alternative teaching formats in counseling, especially HyFlex. This article serves as a foundation for learning those teaching methods and may provide some insight into the variables that determine effective teaching.…”
mentioning
confidence: 99%